What Knowledge Is Most Worth Knowing- For Economics Majors? - Hansen, W. Lee (American Economic Review, 2016)
asks it in a new context. The old question is a paraphrase of the title of Herbert Spencer's famous essay What Knowledge is of Most Worth? The new context is to pose the question for undergraduate students majoring in economics. My intent is to engage you in reflecting about what kinds of knowledge and skills our economics majors should master-what proficiencies they should be able to demonstrate-by the time they graduate from college. My focus is on not the select few who plan to enter graduate economics programs, but rather the vast majority who go out into the world and will become the next generation of leaders. I propose a list of knowledge and skills, perhaps a better word is proficiencies, that we might reasonably expect our majors to demonstrate upon graduation. This is by no means a final or definitive list; rather it is offered to stimulate discussion about the meaning of the economics major and how to give it more meaning.